Local Integration and Congolese Forced Migrants in Dar es Salaam, Tanzania - Pangilinan, Christian (African Human Mobility Review, 2021)
Thousands of unregistered Congolese forced migrants live in Dar es Salaam, Tanzania. Some of them have lived in the city for years but their long-term futures remain undecided. Although many originally arrived for asylum-related reasons, the vast majority are not recognised as refugees or have only temporary legal status. In the context of discussions over possible legal solutions or residency for such people, this paper relies on interviews, focus groups and a survey of Congolese forced migrants in Dar es Salaam to ascertain their views on local integration as a possible option; local integration being a traditional permanent solution to the search for refuge. Results indicate that many Congolese forced migrants are locally integrated to a significant extent, although many continue to face significant challenges in terms of discrimination, economic self-sufficiency, safety and education. The paper concludes that, in light of their preferences and their degree of integration, there should be a variety of policy options for Congolese forced migrants. Some Congolese forced migrants indicate that asylum is a desired solution, some prefer naturalisation, or temporary legal residence, and some even consider assistance towards repatriation to be acceptable.